Criminal Law Reform in Addressing the Gratification Loophole Disguised as Grants - Sulaiman Amiruddin; Megawati Barthos (International Journal Labs, 2024)
This study aims to analyze the legal loopholes that exist in the regulation of gratification and grants in Indonesia, as well as the implications of these loopholes for the integrity of the legal system and public trust in the government. Using a normative legal approach, this study explores the definition, scope, and fundamental differences between gratification and grants under the provisions of applicable laws. The results of the study indicate that the ambiguity in these regulations has facilitated the practice of gratification disguised as grants, thereby reducing the effectiveness of law enforcement. This study recommends reforming the criminal law that includes a clearer and more comprehensive definition as well as a stricter oversight mechanism to prevent abuse and create a more transparent and accountable legal system.